A dual-purpose humanized mouse model for testing antiviral strategies against both SIV and HIV - Barnett, Ella; Kaginkar, Snehal; Schmitt, Kimberly; Remling-Mulder, Leila; Akkina, Ramesh (Frontiers in Immunology, 2024)
Nonhuman primate (NHP) models employing simian/simian-human immunodeficiency viruses (SIV/SHIVs) played a major role in the study of HIV pathogenesis, latency, and cure studies in a preclinical setting. However, it took many years to arrive at the current effective triple drug ARV regimen against SIV due to the genetic differences with that of HIVs. Since new combinations of drugs will be used in the evolving HIV cure studies, a small animal model would be ideal to determine their efficacy against the commonly used SIVs such as SIVmac239 to triage ineffective drugs prior to their application in NHPs. We recently determined that humanized mice (hu-mice) with a transplanted human immune system are permissive to SIVmac strains in addition to HIVs. Based on this novel finding, here we evaluated the utility of this dual-purpose hu-mouse model to test different ART regimens against SIVmac239. Infected mice showing chronic viremia were treated with a combination anti-retroviral treatment (cART) regimen consisting of of FTC/EVG/TDF (emtricitabine/elvitegravir/tenofovir disoproxil fumarate (FTC/EVG/TDF)). Full viral suppression was seen for several weeks in SIVmac239-infected and treated mice similar to that seen with the HIV-1 BaL virus used as a control. However, viral rebound was eventually observed in SIVmac239 infected mice during the treatment period, suggesting viral escape compared to HIV-1 BaL with which viral suppression was fully sustained. Next, a cART regimen consisting of emtricitabine/bictegravir/tenofovir alafenamide fumarate (FTC/BIC/TAF) was similarly evaluated. Our results showed that this ARV regimen was fully effective in rapidly suppressing both SIVmac239 and HIV-1 BaL. Complete viral suppression was maintained until treatment interruption after which viral loads rebounded. These findings highlight the utility of humanized mice for in vivo screening of new combinations of ARV compounds against various SIVs prior to employing them in NHPs. In addition to identifying new effective cART regimens against SIVs, this model would also be amenable to evaluating immunotherapeutic strategies using broadly neutralizing antibodies, LRAs and novel therapeutics in comparative cure studies of SIV and HIV.